2019
DOI: 10.1002/jor.24429
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Perforation Risk in Plate Osteosynthesis of Unstable Proximal Humerus Fractures: A Biomechanical Investigation of the Effect of Screw Length

Abstract: Secondary perforation of screws into the joint surface is a commonly reported mechanical fixation failure mode in locked plating of proximal humerus fractures (PHF). This study investigated the influence that screws tip to joint distance (TJD) has on the biomechanical risk of secondary screw perforation and the stability of PHF. Ten pairs of cadaveric proximal humeri with a wide range of bone mineral density were used. Each specimen was osteotomized and instrumented with the PHILOS plate, simulating a highly u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…These investigations demonstrate that longer screws provide a stronger fixation. It is generally accepted that the distance between the tip of the screw and the articular surface should be 5–8 mm ( Ciric et al, 2019 ). Using a longer screw within this range can prevent the screw from loosening without increasing the risk of screw penetration.…”
Section: Discussionmentioning
confidence: 99%
“…These investigations demonstrate that longer screws provide a stronger fixation. It is generally accepted that the distance between the tip of the screw and the articular surface should be 5–8 mm ( Ciric et al, 2019 ). Using a longer screw within this range can prevent the screw from loosening without increasing the risk of screw penetration.…”
Section: Discussionmentioning
confidence: 99%
“…A recent series made by Ciric et al . reported that placing calcar screws closely to the subchondral bone of humerus head did not increase the risk of screw loosening 34 . In contrast, placing short calcar screws could lead to screw loosening and secondary varus deformity.…”
Section: Discussionmentioning
confidence: 99%
“…A recent series made by Ciric et al reported that placing calcar screws closely to the subchondral bone of humerus head did not increase the risk of screw loosening. 34 In contrast, placing short calcar screws could lead to screw loosening and secondary varus deformity. In a finite element analysis of Yang et al, it pointed out that with the absence of medial support, the intense pressure near the calcar screws of the locking plate contributed to the high rate of plate breakage and iatrogenic fractures.…”
Section: Importance and Methods For Recovery Of Medial Supportmentioning
confidence: 99%